Cortical branches of the middle cerebral artery in silver fox (Vulpes vulpes) - Skoczylas,Benedykt (2016)
ABSTRACT: The study of the vascularization of the cerebrum in silver fox was performed on 80 cerebral hemispheres. It was found that the middle cerebral artery is the strongest vessel supplying blood to the cerebrum. The artery gets divided into ten permanent branches. Two olfactory arteries supply the region of the cerebrum located on the border between the old and the new cortex. The other eight supply the region of the new cortex. The frontal, parietal and temporal branches descended independently from the main trunk of the middle cerebral artery or formed a common trunk. Common trunks for respective groups of branches have been described as the anterior, superior and posterior middle cerebral artery. The alterior olfactory artery in 5% of cases and posterior olfactory artery in 2.5% of cases were independent branches of the middle cerebral artery extending from the rostral cerebral artery.